2023
DOI: 10.1021/acsnano.3c03385
|View full text |Cite
|
Sign up to set email alerts
|

Effective Orthodontic Tooth Movement via an Occlusion-Activated Electromechanical Synergistic Dental Aligner

Qian Wang,
Jie Zhang,
Guang Yao
et al.

Abstract: Malocclusion is a prevalent dental health problem plaguing over 56% worldwide. Mechanical orthodontic aligners render directional teeth movement extensively used for malocclusion treatment in the clinic, while mechanical regulation inefficiency prolongs the treatment course and induces adverse complications. As a noninvasive physiotherapy, an appropriate electric field plays a vital role in tissue metabolism engineering. Here, we propose an occlusionactivated electromechanical synergistic dental aligner that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Figure 6 a–d illustrates the working mechanism of piezoelectric force sensors [ 76 , 122 , 125 , 151 , 152 , 163 , 182 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 ] and introduces several representative structural design strategies (e.g., fiber arrays, stacked layers, rigid-soft hybrid structure) of sensor architecture. Specifically, Persano et al utilized high-density arrays of aligned piezoelectric nanofibers (e.g., P(VDF-TrFe)) to develop a piezoelectric force sensor with large area (tens of cm 2 ) ( Figure 6 b) [ 163 ].…”
Section: Structures and Applications For Different Types Of Force Sen...mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 a–d illustrates the working mechanism of piezoelectric force sensors [ 76 , 122 , 125 , 151 , 152 , 163 , 182 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 ] and introduces several representative structural design strategies (e.g., fiber arrays, stacked layers, rigid-soft hybrid structure) of sensor architecture. Specifically, Persano et al utilized high-density arrays of aligned piezoelectric nanofibers (e.g., P(VDF-TrFe)) to develop a piezoelectric force sensor with large area (tens of cm 2 ) ( Figure 6 b) [ 163 ].…”
Section: Structures and Applications For Different Types Of Force Sen...mentioning
confidence: 99%
“…However, it remains challenging to improve the sensors performance from multiple aspects simultaneously and realize the on-demand design of mechanical force sensors for specific application scenarios. As shown in Figure 1 , many applications in healthcare and diagnosis are opened up by developments of flexible mechanical force sensors, including pulse wave [ 110 , 111 , 112 , 113 , 114 , 115 ] and muscle softness detection [ 116 ], ICP and IOP measurement [ 117 , 118 , 119 ], throat and cardiac activity monitoring [ 55 , 120 ], abdomen and pulse diagnoses [ 121 , 122 ], as well as force sensing in orthotics [ 123 , 124 ], orthodontics [ 125 ] and skin-prosthesis interface [ 64 ]. While many excellent reviews of flexible pressure sensors can be found in the literature [ 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 ], they focus mainly on the working mechanisms, material selections and device performances.…”
Section: Introductionmentioning
confidence: 99%
“…However, OTM is not just a mechanical process; it also involves an inflammatory response and can cause tooth pain, also known as orthodontic pain (Zainal Ariffin et al., 2011 ). Additionally, OTM can result in changes in dental occlusion, which is the way the upper and lower teeth come together when biting or chewing (Wang et al., 2023 ). Individual responses to OTM differ markedly, with some patients acclimating smoothly to the process, whereas others might endure considerable discomfort or struggle with the adjustments in bite occlusion (Cioffi, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…For fabricating electrodes, adopting Cu/PI organic-inorganic composite can help improve deformability when maintaining essential conductivity 24,25 . It is also necessary to design specific structures (e.g., serpentine) of the electrodes to enable the tensile strength 26 . In order to enhance the adhesion of flexible electronics to facial skin, silk, poly(N-isopropylacrylamide) (PNIPAM), and other materials can be used to modify hydrogels to increase the covalent and non-covalent interactions 21 , while some other flexible electronics used to detect physical and biological signals in the oral cavity are mainly attached to mouth guards by using medical-grade epoxy or pastes [27][28][29] .…”
mentioning
confidence: 99%
“…For example, the modified polyaniline (PANI) and PVB with increased porous structures coated on electrodes can enhance their ability to enrich ions, thereby boosting the sensitivity of the sensing process 31 . In addition, improving the electrode patterns or array shapes can also improve the sensitivity 21,26 .…”
mentioning
confidence: 99%